Collaborative Governance in the Public Service Sector: A Bibliometrics Analysis - Putu Jaya Adnyana Widhita; Vishnu Juwono; Muh Azis Muslim (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
In the modern era, governance can no longer operate effectively through a purely hierarchical and top-down approach. The complexity of social, economic, and environmental challenges faced by society demands a more inclusive and responsive framework. In line with contemporary public service demands, it is imperative to examine collaborative governance in public services to understand how diverse stakeholders can synergize effectively to address intricate public issues, optimize service delivery, and enhance governmental legitimacy and responsiveness. The purpose of this paper is to provide an overview of numerous research projects concerning collaborative governance in public services. Using VOSViewer as an analytical tool, we present the findings of our bibliometric analysis. Based on data from the Scopus database, covering the period from 2004 to 2025, a total of 76 English-language articles were identified. The highest number of publications—11 papers—was recorded in 2025 (up to July). The most cited document received 145 citations, and the country producing the highest number of articles on collaborative governance in public services is the United States, with 22 publications and 708 citations.